Prevent Osteoporosis Early: Nutrition Education and Yoga-Based Physical Exercise for Women Aged 30+ In the Dawuhan Housing Community, Purbalingga: Pengabdian - Ema Wahyu Ningrum; Ikit Netra Wirakhmi; Khusnul Muflikhah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Osteoporosis is a degenerative disease that is a serious problem, especially in women aged 30 years and above. Risk factors include low calcium intake, lack of physical activity, and a sedentary lifestyle. Observations at the Dawuhan Women's Association in Padamara District, Purbalingga Regency, revealed low awareness, calcium consumption, and exercise habits among members. In response, a community service program for early prevention through promotive-preventive education was implemented. Methods included balanced nutritional counseling, yoga-based physical exercise, and pre- and post-tests. Activities included education on risk factors, training in reading nutrition labels and selecting calcium-rich foods, and yoga practices for bone health, involving lecturers, students, nutritionists/physiotherapists, and sports instructors. Results showed a significant increase in participants' knowledge and motivation in maintaining nutrition and physical activity. This program effectively empowers women to maintain bone health and has the potential to become a sustainable model for osteoporosis prevention in the community.